Persistent puzzles: The philosophy and ethics of private corrections in the context of contemporary penality. Issue 2 (12th May 2019) - Sparks, Richard; Gacek, James
Abstract : Research Summary: In our article, we attend to the implied outlooks ("philosophies" in the sense of operative practical discourses and assumptions) and the competing ethical concerns that animate differing views on privatizing corrections. We consider some normative arguments and empirical observations that have been mobilized for and against privatization since the inception of the modern version of this debate in the late 1980s, and we seek to place these in the context of accounts of penal problems over that contentious period. We argue that a multidimensional approach to understanding the sociology of punishment and in particular how certain forms of punishment persist, survive, and thrive is required when considering the privatization of corrections. In using such an approach, we raise quizzical questions regarding the pairing together of punishment and privatization, and as a result, we seek to sharpen the discussion about future prospects. Policy Implications: Greater attention must be paid toward public involvement, knowledge, and understanding about penal policies. With particular regard to the involvement of private‐sector actors and interests, this has implications both at the initial contract negotiation stages of expanding correctional privatization as well as at the rescission of such contracts. The impact of penal arrangements on the dignity and integrity of offenders—especially but not only prison inmates—their loved ones and communities, and wider considerations of public interest are abiding and unresolved concerns, and privatization policies must be evaluated in light of these.